2008
DOI: 10.1007/s00464-008-0257-6
|View full text |Cite
|
Sign up to set email alerts
|

Safe and feasible inflow occlusion in laparoscopic liver resection

Abstract: Laparoscopic Pringle's maneuver using an Endo Retract Maxi can be performed easily for all patients undergoing laparoscopic liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…1,23,24 In conclusion, the Tri-Staple technology in laparoscopic liver resection is safe and feasible for the resection of liver segments. The contribution of this new technology and a completed learning curve account for a favorable outcome with minimal morbidity especially when approaching P-S segments and in complex cases of major hepatectomy.…”
Section: Discussionmentioning
confidence: 83%
“…1,23,24 In conclusion, the Tri-Staple technology in laparoscopic liver resection is safe and feasible for the resection of liver segments. The contribution of this new technology and a completed learning curve account for a favorable outcome with minimal morbidity especially when approaching P-S segments and in complex cases of major hepatectomy.…”
Section: Discussionmentioning
confidence: 83%
“…Most surgical teams use a 10-14 mmHg pneumoperitoneum [13][14][15][16][17][18][19][20][21][22][23][24], which allows a good control of bleeding (Grade C). In a case-match analysis Tranchart et al [6] suggested that the positive pressure of pneumoperitoneum was probably the main factor explaining the decreased blood loss during laparoscopy when compared to open liver surgery (Grade C).…”
Section: Pneumoperitoneummentioning
confidence: 99%
“…1) or Endo Mini-Retract (Covidien Japan, Tokyo, Japan) to be used as a tourniquet for complete interruption of blood inflow to the liver only if necessary [9]. www.intechopen.com 2.1 Encircling right-sided Glissonean pedicles, including the right, anterior, and posterior pedicles After dividing the cystic artery and duct and dissecting the gallbladder neck, the peritoneum of the hepatoduodenal ligament is dissected at the hepatic hilum (Fig.…”
Section: Surgical Techniquementioning
confidence: 99%